2022
DOI: 10.4103/ijo.ijo_1124_22
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative optical coherence tomography-guided donor corneal tissue assessment and preparation

Abstract: Purpose: To evaluate the role of intraoperative optical coherence tomography (i-OCT) in donor grading, selection, and preparation during different types of keratoplasty. Methods: Seventy-one consecutive donor corneas collected over 6 months, after clinical grading, were observed by an experienced corneal surgeon under an i-OCT equipped microscope. The donor preparation (manual/automated) for different types of keratoplasty procedures was also undertaken under i-OCT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…During graft preparation, either one or two consecutive passes of a microkeratome blade allow for the creation of a very thin lenticule in a procedure known as UltraThin-DSAEK (UT-DSAEK), which has become the standard modern approach to DSAEK [40,45,46]. In cases in which this preparation is carried out in the operating room rather than at the eye bank, iOCT allows the surgeon to easily check the residual stromal thickness, the smoothness of the cut, and the regularity of the UT-DSAEK lenticule [47][48][49][50][51] (Figure 3).…”
Section: Guiding Ultra-thin Descemet Stripping Automated Endothelial ...mentioning
confidence: 99%
See 1 more Smart Citation
“…During graft preparation, either one or two consecutive passes of a microkeratome blade allow for the creation of a very thin lenticule in a procedure known as UltraThin-DSAEK (UT-DSAEK), which has become the standard modern approach to DSAEK [40,45,46]. In cases in which this preparation is carried out in the operating room rather than at the eye bank, iOCT allows the surgeon to easily check the residual stromal thickness, the smoothness of the cut, and the regularity of the UT-DSAEK lenticule [47][48][49][50][51] (Figure 3).…”
Section: Guiding Ultra-thin Descemet Stripping Automated Endothelial ...mentioning
confidence: 99%
“…Finally, iOCT can also help in the preparation of the graft as well as in teaching novice surgeons. In fact, iOCT has been used to quantitatively assess the quality of donor corneas and pre-stripped grafts and to monitor each step of the stripping procedure [47,48]. Likewise, wet labs equipped with microscope-integrated iOCT allow expert surgeons to monitor the progression of their pupils and correct them accordingly [77].…”
Section: Guiding Descemet Membrane Endothelial Keratoplastymentioning
confidence: 99%
“…Anterior segment optical coherence tomography (OCT), one of the most useful instruments in ophthalmic imaging, was used to measure corneal shape, corneal morphology, corneal thickness, and corneal curvature. [28,29]. On day 7 after surgery, the anterior Anterior segment optical coherence tomography (OCT), one of the most useful instruments in ophthalmic imaging, was used to measure corneal shape, corneal morphology, corneal thickness, and corneal curvature [28,29].…”
Section: In Vivo Biocompatibility Assaymentioning
confidence: 99%
“…[28,29]. On day 7 after surgery, the anterior Anterior segment optical coherence tomography (OCT), one of the most useful instruments in ophthalmic imaging, was used to measure corneal shape, corneal morphology, corneal thickness, and corneal curvature [28,29]. On day 7 after surgery, the anterior segment OCT showed that the Col-EDC-PRA adhered to the residual corneal stromal bed, with a clearly visible interface and higher density compared to the cornea.…”
Section: In Vivo Biocompatibility Assaymentioning
confidence: 99%